KONSEP WASIAT DALAM PERSPETIF HUKUM ISLAM - Maimun Maimun (State of Islamic Institute Langsa, 2017)
In Islam, the wasiyat is not merely a matter of property. In the broadest sense, the wasiyat also deals with moral messages to mankind. In the Qur'an, Allah Almighty Himself has reminded that believers always have a wasiyat in virtue and patience. This verse affirms that a person who is about to die must necessarily leave a wasiyat to his possessions, this verse may also serve as a legal basis (mandatory) of the wasiyat, particularly to the heirs whose liaison with the heir is cut off, become walled up caused by other heirs, such as the case of a grandchild who is wallowed to get the inheritance of the datuk (his grandfather) due to his uncle (his father's siblings) still exist. The will for the non-heirs required to fulfill the maximum amount is 1/3 of the property left behind, after deducting the cost of holding the corpse and repayment of the debts. The law of wasiyat origin can not be more than 1/3 of the inheritance. If more than 1/3 of the property, then it depends on the heirs, if they allow it can be implemented, if not then carried out only related 1/3 of the treasure alone, Wasiyat is one means to approach Allah swt in order to get goodness in the world and the reward in the hereafter. Wasiyat is also a means to provide assistance to people in need, strengthening friendships and kinship relations that are not his heirs. The law of wasiyat when examining Surat al-Baqarah verse 180 is obligatory in accordance with the textual meaning of that verse.